Peningkatan Kapasitas Mahasiswa Kesejahteraan Sosial melalui Program MSIB di BSPS Kementerian PUPR Sumatera Utara - Ade Indah Hutasoit; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
Housing development and community empowerment are two crucial pillars in enhancing social welfare in Indonesia. The Certified Internship and Independent Study Program (MSIB), launched by the Ministry of Education, Culture, Research, and Technology, aims to provide real-world work experience for students. In the Ministry of Public Works and Public Housing (PUPR) in North Sumatra Province, the MSIB program offers Social Welfare (Kessos) students the opportunity to engage in the BSPS (Self-Help Housing Assistance) program for five months. This study uses a descriptive qualitative approach to evaluate the capacity building of Kessos students through the MSIB program. The findings indicate that students acquire technical skills such as project management and social analysis, as well as non-technical skills like work ethics, effective communication, and teamwork. The Community Organization and Community Development (COCD) method used during the internship helps students understand the importance of a participatory approach in working with communities. The MSIB program not only enhances the individual capacities of students but also contributes to curriculum updates at universities and improvements in social welfare in Indonesia. Thus, this program prepares Kessos students to become professional and effective social workers.